2016
DOI: 10.3904/kjim.2015.253
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of alcoholic liver disease (ALD)/nonalcoholic fatty liver disease (NAFLD) index combined with γ-glutamyl transferase in differentiating ALD and NAFLD

Abstract: Background/Aims:This study aimed to verify the reliability of the alcoholic liver disease (ALD)/nonalcoholic fatty liver disease (NAFLD) index (ANI) for distinguishing ALD in patients with hepatic steatosis from NAFLD, and to investigate whether ANI combined with γ-glutamyl transferase (GGT) would enhance the accuracy of diagnosis in China.Methods:A hundred thirty-nine cases of fatty liver disease (FLD) were divided into two groups of ALD and NAFLD. The ANI was calculated with an online calculator. All indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 34 publications
(36 reference statements)
2
15
0
3
Order By: Relevance
“…19 The De-ritis ratio was higher in patients with ALD (2.49±0.8) than that of NAFLD (0.87±0.27). Serum AST level was significantly higher than ALT in ALD groups which gave rise to higher De-ritis ratio, and this was similar to the studies done by Ram, et al 21 Junking, et al 1 Serum ALT is usually higher than AST in most causes of liver damage, but AST remains significantly higher in case of ALD. This might be because AST is a mitochondrial enzyme, acetaldehyde and free radicals produced during ethanol metabolism can lead to oxidative stress and lipid peroxidation causing mitochondrial injury which results in leakage of AST in the circulation as mAST is the more prevalent isoenzyme with approximately 80% of total AST activity in human liver contributed by mAST.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…19 The De-ritis ratio was higher in patients with ALD (2.49±0.8) than that of NAFLD (0.87±0.27). Serum AST level was significantly higher than ALT in ALD groups which gave rise to higher De-ritis ratio, and this was similar to the studies done by Ram, et al 21 Junking, et al 1 Serum ALT is usually higher than AST in most causes of liver damage, but AST remains significantly higher in case of ALD. This might be because AST is a mitochondrial enzyme, acetaldehyde and free radicals produced during ethanol metabolism can lead to oxidative stress and lipid peroxidation causing mitochondrial injury which results in leakage of AST in the circulation as mAST is the more prevalent isoenzyme with approximately 80% of total AST activity in human liver contributed by mAST.…”
Section: Resultssupporting
confidence: 89%
“…Studies have shown that GGT has higher predictive value of ALD. 1,18,20 Increase in serum levels of ALP along with GGT suggests a liver pathology. 19 The De-ritis ratio was higher in patients with ALD (2.49±0.8) than that of NAFLD (0.87±0.27).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Liver diseases, affecting more than 10% of the world population, remains one of the most serious public health concerns worldwide [ 1 ]. Among the various forms of liver disease, alcoholic liver disease (ALD) and non-alcoholic fatty liver disease (NAFLD) are the two most common types with high prevalence around the world [ 2 ]. ALD, resulting from chronic excessive alcohol consumption, is one of the most important causes of liver-related death, accounting for an estimated 3.8% of global mortality [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…ALD is caused by excessive alcohol consumption whereas NAFLD is related with obesity and metabolic disorders, although nonalcoholic steatohepatitis (NASH) has been reported in lean individuals [3]. Both ALD and NAFLD may progress into fibrosis, cirrhosis, and eventually hepatocellular carcinoma as a result of severe and prolonged liver damage [4]. The effect of current synthetic agents in treating ALD and NAFLD is not satisfactory and most of them have undesirable side effects [5].…”
Section: Introductionmentioning
confidence: 99%